DESAIN SIMULASI SISTEM PENGATURAN KECEPATAN MOTOR INDUKSI TIGA FASA DENGAN SWITCHING SPACE VECTOR PULSE WIDTH MODULATION - Muhamad Yusuf; Vicky Prasetia; Sugeng Dwi Riyanto; Arif Ainur Rafiq (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2019)
Induction motor has been used by industry as a source of mechanical energy. Induction motors are very reliable, inexpensive, and easy to maintain. Induction motor is difficult to control because one of the nonlinear plant categories. The method can be used to regulate the speed of an induction motor is to set the vector. In order for an induction motor to be easily controlled like a separate dc booster motor, the induction motor is modeled in the rotary axis reference (d-q model). This research applies an induction motor speed regulation scheme using Switching Space Vector Pulse Width Modulation (SVPWM). This system produces a steady state error averaging below 4 (four) rpm or equal to 0.3% with a load torque of between 5 Nm to 35 Nm.